2005
DOI: 10.1161/circulationaha.105.540500
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Inhibits β-Adrenergic–Stimulated Cardiac Contractility in Humans

Abstract: Background-Sildenafil inhibits phosphodiesterase 5 (PDE5A) to elevate intracellular cGMP and to induce vasodilation.This effect has led to its use for treating erectile dysfunction. Although its influence on rest heart function has appeared minimal, recent animal studies suggest that sildenafil can have potent effects on hearts stimulated by ␤-adrenergic or pressure overloads. We therefore tested whether sildenafil blunts dobutamine-stimulated cardiac function in humans. Methods and Results-Thirty-five healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(132 citation statements)
references
References 51 publications
2
128
2
Order By: Relevance
“…Experimental models of isolated cardiomyocytes and perfused rodent hearts, and human studies of normal and heart failure patients at the time of cardiac catheterisation, have shown that elevated levels of cGMP (produced through inhaled inducible NO or oral sildenafil) can suppress contractility by decreasing myocardial calcium sensitivity, inhibiting cyclic adenosine monophosphate and blunting the contractile response to adrenergic stimulation [17,[22][23][24]. Although peri-operative cGMP was similar between groups in this study, alterations to cyclic adenosine monophosphate, myocardial calcium handling and endogenous catecholamine levels were not investigated and could account for the significant contractile deficit in sildenafil patients.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental models of isolated cardiomyocytes and perfused rodent hearts, and human studies of normal and heart failure patients at the time of cardiac catheterisation, have shown that elevated levels of cGMP (produced through inhaled inducible NO or oral sildenafil) can suppress contractility by decreasing myocardial calcium sensitivity, inhibiting cyclic adenosine monophosphate and blunting the contractile response to adrenergic stimulation [17,[22][23][24]. Although peri-operative cGMP was similar between groups in this study, alterations to cyclic adenosine monophosphate, myocardial calcium handling and endogenous catecholamine levels were not investigated and could account for the significant contractile deficit in sildenafil patients.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it can be explained by reflex sympathetic stimulation caused by vasodilation. Indeed, in humans, sildenafil reduces vagal modulation and increases sympathetic stimulation of the heart [187] and also slightly increases contractility in healthy human volunteers [188] although the effect in this study is suspect since the measurements were taken 75 min follow ing dobutamine infusion. Sildenafil-induced sympathetic activation seems to be general, as shown by increases in plasma norepinephrine levels and muscle sympathetic nerve activity [189] .…”
Section: Regulation Of Myocardial Contractility By Pde5mentioning
confidence: 80%
“…This effect was not observed in eNOS knockout mice but was restored with adenoviral transfer of active eNOS [181] . Sildenafil also slightly attenuated the isoproterenol-induced increase in force of contraction in human myocardial tissue [190] , and contractile response to dobutamine was blunted by sildenafil in healthy human volunteers [188] .…”
Section: Regulation Of Myocardial Contractility By Pde5mentioning
confidence: 95%
“…PDE5A inhibitors attenuate adrenergic stimulation [209], reduce ventricularvascular stiffening [209], antagonize maladaptive chamber …”
Section: Phosphodiesterase Type 5 Inhibition (Pde5-i)mentioning
confidence: 99%